Pangenome analysis of Corynebacterium striatum: insights into a neglected multidrug-resistant pathogen - Nageeb, Wedad M.; Hetta, Helal F. (BMC microbiology, 2023)
Over the past two decades, Corynebacterium striatum has been increasingly isolated from clinical cultures with most isolates showing increased antimicrobial resistance (AMR) to last resort agents. Advances in the field of pan genomics would facilitate the understanding of the clinical significance of such bacterial species previously thought to be among commensals paving the way for identifying new drug targets and control strategies. We constructed a pan-genome using 310 genome sequences of C. striatum. Pan-genome analysis was performed using three tools including Roary, PIRATE, and PEPPAN. AMR genes and virulence factors have been studied in relation to core genome phylogeny. Genomic Islands (GIs), Integrons, and Prophage regions have been explored in detail. The pan-genome ranges between a total of 5253-5857 genes with 2070 - 1899 core gene clusters. Some antimicrobial resistance genes have been identified in the core genome portion, but most of them were located in the dispensable genome. In addition, some well-known virulence factors described in pathogenic Corynebacterium species were located in the dispensable genome. A total of 115 phage species have been identified with only 44 intact prophage regions. This study presents a detailed comparative pangenome report of C. striatum. The species show a very slowly growing pangenome with relatively high number of genes in the core genome contributing to lower genomic variation. Prophage elements carrying AMR and virulence elements appear to be infrequent in the species. GIs appear to offer a prominent role in mobilizing antibiotic resistance genes in the species and integrons occur at a frequency of 50% in the species. Control strategies should be directed against virulence and resistance determinants carried on the core genome and those frequently occurring in the accessory genome.